Implementasi Metode Takror dalam Membentuk Kedisiplinan Belajar Santri di Pondok Modern Darul Ihsan Payaman Nganjuk - Lailatul Magfiroh; A Jauhar Fuad (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study investigates how the takror method is implemented and how it contributes to students’ learning discipline at Darul Ihsan Modern Islamic Boarding School Payaman Nganjuk. Although takror is widely practiced in Islamic boarding schools, its role in fostering learning discipline has received limited scholarly attention. This qualitative study employed a case study design. Data were collected through observations, interviews, and documentation involving school administrators, class supervisors, dormitory supervisors, and students. The findings show that takror is conducted regularly every evening through reviewing previous lessons and preparing upcoming materials under close supervision. The method enhances students’ learning discipline by improving schedule adherence, learning responsibility, class readiness, and time management. The study concludes that the takror method functions not only as a learning strategy but also as an effective approach to developing disciplined character in the Islamic boarding school environment.